ALTERNATE HISTORY IN KAZUO ISHIGURO’S WHEN WE WERE ORPHANS - Kumar, Suresh; Bose, A. Xavier Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kazuo Ishiguro, the Japanese born British author’s fifth novel, When We Were Orphans is set mostly against the historical events such as the International Settlement in Shanghai, China, the Second Sino - Japanese War, Opium Trade in China, the Civil War between the Communists and the Nationalists in China and Japan’s invasion of China. These historical contexts furnish Ishiguro a platform to fabricate untold events. The past and the present events jump back and forth. The first-person narrator and the other characters heavily rely on their memory to describe the past. This article tries to discover how far the subjective perspective of history has been used by Ishiguro in reconstructing the historical events by mingling public history with personal history of the protagonist, Christopher Banks, a remarkable private detective.